Synthesis and deposition of bismuth oxychloride with a rose-type flower shape and photoelectroactivity evaluation in the methyl orange discoloration reaction - Pelissari, Marcelo Rodrigues da Silva [UNESP]; Pereira Camargo, Luan; Pontes, Fenelon Martinho Lima [UNESP]; Dall'Antonia, Luiz Henrique (Wiley, 2023)
In this work, bismuth oxychloride with a rose-type flower shape was successfully synthesised using the easy and low-cost successive ionic layer adsorption and reaction process. The tetragonal crystalline structure with a flower-like shape and thickness of 150-nm nanosheets was used as electrode material in an exciting approach for the photoelectrochemical discoloration reaction of methyl orange. The structure, morphology and optical properties of the obtained bismuth oxychloride sample were evaluated through X-ray diffraction, Raman spectroscopy, the Brunauer–Emmett–Teller method, diffuse reflectance ultraviolet–visible spectroscopy and scanning electron microscopy. Through photoelectrochemical characterisation measurements (linear sweep voltammetry, chronoamperometry and electrochemical impedance spectroscopy techniques), the bismuth oxychloride electrode showed remarkable electroactivity under ultraviolet light irradiation. The methyl orange discoloration reaction, performed under ultraviolet light incidence and potential application of −0.5 V (vs silver/silver chloride) for 60 minutes, produced a higher degradation percentage (ca. 82%) and kobs of 29 × 10−3 min−1.